2D:4D and Self-Employment Using SOEP Data: A Replication Study - Frank M. Fossen; Levent Neyse; Magnus Johannesson; Anna Dreber Almenberg (Institute of Labor Economics (IZA), 2020)
The 2 D:4D digit ratio, the ratio of the length of the 2nd digit to the length of the 4th digit, is often considered a proxy for testosterone exposure in utero. A recent study by Nicolaou et al. (2018) reported an association between the lefthand 2D:4D and self-employment (in a sample of about 1,000 adults). In this preregistered study we replicate these results on a new and larger sample of about 2,600 adults from the German Socioeconomic Panel-Innovation Sample (SOEP-IS). We find no statistically significant associations between 2D:4D and self-employment and thus cannot confirm the findings of Nicolaou et al. (2018) for left-hand 2D:4D. Our estimated 99.5% confidence intervals are within an about 2 percentage points change in self-employment for a one standard deviation change in the 2D:4D when we pool results for men and women (the association does not differ significantly between men and women). Even larger studies are needed to rule out smaller effect sizes.
Keywords: J23; L26; 330; hormones; entrepreneurship; self-employment; testosterone; digit ratio